Serine Supports IL-1β Production in Macrophages Through mTOR Signaling - Chen, Siyuan; Xia, Yaoyao; He, Fang; Fu, Jian; Xin, Zhongquan; Deng, Baichuan; He, Liuqin; Zhou, Xihong; Ren, Wenkai (Frontiers in Immunology, 2020)
Intracellular metabolic programs tightly regulate the functions of macrophages, and previous studies have shown that serine mainly shapes the macrophage function via one-carbon metabolism. However, it is unknown whether serine modulates the macrophage function independent of one-carbon metabolism. Here, we find that serine deprivation lowers interleukin (IL)-1β production and inflammasome activation, as well as reprograms the transcriptomic and metabolic profile in M1 macrophages. Intriguingly, supplementation of formate, glycine, dNTPs, and glucose cannot rescue the production of IL-1β from serine-deprived macrophages. Mechanistically, serine deprivation inhibits macrophage IL-1β production through inhibition of mechanistic target of rapamycin (mTOR) signaling. Of note, the macrophages from mice feeding serine-free diet have lower IL-1β production, and these mice also show less inflammation after LPS challenge. Collectively, our data highlight a new regulatory mechanism for serine to modulate the macrophage function.